THE INFLUENCE OF LEADERSHIP STYLE ON TEACHER LOYALTY THROUGH WORK DISCIPLINE IN MIDDLE SCHOOLS AT THE ESA PRAKARSA EDUCATION FOUNDATION LANGKAT DISTRICT - Syahrizal Syahrizal; Mesra B (Penerbit Lafadz Jaya, 2023)
The purpose of this study was to determine and analyze the effect of leadership style on teacher loyalty mediated by work discipline in secondary schools at the Esa Prakarsa Education Foundation, Langkat Regency. This research was conducted at the Esa Prakarsa Education Foundation, Langkat Regency. The type of research is associative quantitative. The population in this study were 80 teachers. The sampling technique in this study used a saturated sample where the entire population was sampled. The results of this study indicate that leadership style has no significant effect on teacher loyalty, but has a significant effect on improving teacher work discipline. Teacher work discipline is also proven to have a positive and significant effect on teacher loyalty. In the indirect effect it was found that work discipline was able to mediate the effect of leadership style on teacher loyalty significantly. This finding indicates that although leadership style does not directly affect teacher loyalty, through improving teacher work discipline, the impact can be mediated so that it contributes to increasing teacher loyalty. Therefore, teacher work discipline has an important mediating role in linking leadership style with teacher loyalty in the Esa Prakarsa Education Foundation Middle School, Langkat Regency. These findings provide important insights for the development of leadership and management strategies in educational institutions to improve work discipline which will ultimately have an impact on teacher loyalty.